Microsaccades and covert attention: Evidence from a continuous, divided attention task - Aimee Elizabeth Ryan; Brendan Keane; Guy Wallis (Journal of Eye Movement Research)
A substantial question in understanding expert behavior is isolating where experts look, and which aspects of their environment they process. While tracking the position of gaze provides some insight into this process, our ability to attend covertly to regions of space other than the current point of fixation, severely limits the diagnostic power of such data. Over the past decade, evidence has emerged suggesting that microscopic eye movements present during periods of fixation may be linked to the spatial distribution of covert attention, potentially offering a powerful tool for studying expert behavior. To date, the majority of studies in this field have tested the link under the constraints of a trial by trial, forced-response task. In the current study we sought to examine the effect when participants performed a continuous, divided-attention task, with the hope of bridging the gap to a range of more ecological, real-world tasks. We report various aspects of the eye movement and response data including (i) the relationship between microsaccades and drift correction, (ii) response behavior in brief time periods immediately following a microsaccade,         (iii) response behavior briefly preceding a microsaccade. Analysis failed to reveal a link between task accuracy and the direction of a microsaccade. Most striking however, we found evidence for a timelocked relationship between the side of space responded to and the direction of the most recent microsaccade. The paper hence provides preliminary evidence that microsaccades may indeed be used to track the ongoing allocation of spatial attention.